Drug treatment of inborn errors of metabolism: a systematic review. Issue 6 (26th March 2013) - Alfadhel, Majid; Al-Thihli, Khalid; Moubayed, Hiba; Eyaid, Wafaa; Al-Jeraisy, Majed
Abstract : Background: The treatment of inborn errors of metabolism (IEM) has seen significant advances over the last decade. Many medicines have been developed and the survival rates of some patients with IEM have improved. Dosages of drugs used for the treatment of various IEM can be obtained from a range of sources but tend to vary among these sources. Moreover, the published dosages are not usually supported by the level of existing evidence, and they are commonly based on personal experience. Methods: A literature search was conducted to identify key material published in English in relation to the dosages of medicines used for specific IEM. Textbooks, peer reviewed articles, papers and other journal items were identified. The PubMed and Embase databases were searched for material published since 1947 and 1974, respectively. The medications found and their respective dosages were graded according to their level of evidence, using the grading system of the Oxford Centre for Evidence-Based Medicine. Results: 83 medicines used in various IEM were identified. The dosages of 17 medications (21%) had grade 1 level of evidence, 61 (74%) had grade 4, two medications were in level 2 and 3 respectively, and three had grade 5. Conclusions: To the best of our knowledge, this is the first review to address this matter and the authors hope that it will serve as a quickly accessible reference for medications used in this important clinical field.